On the Optimal Target Curbside Parking Occupancy Rate - Richard J. Arnott (Center for Economic Studies and ifo Institute (CESifo), 2013)
For many years, Donald Shoup has been advocating cashing out free and underpriced curbside parking. How should this be implemented in practice, taking into account the stochasticity of curbside parking vacancies? Shoup has proposed setting neighborhood/period of the day-specific meter rates such that a common target (average) curbside parking occupancy rate is achieved. Taking as given how the average occupancy rate affects expected cruising-for-parking time and expected walking time (between parking space and destination), this paper investigates the optimal (surplus-maximizing) target curbside parking occupancy rate. The principal result is that the rate should be higher, the higher is the level of demand.
Keywords: D60; H20; J60; N70; R40; 330; parking; curbside parking; occupancy rate; vacancy rate; pricing